Greetings,

The problem goes like this:

Find all values of x+y, given

3x+5y-6z=2

5xy-10yz-6xz=-41

xyz=6

What I did is I let a=3x, b=5y, and c=-6z.

I let a,b,c be the roots of a poly, and got the poly to be n^3 - 2n^2 - 123n + 540

Sicne it asked for x+y, I let it be in terms of a and b. i found that x+y = (5a+3b)/15.

I used the rational root theorem and used synthetic division one by one of the potential roots, and The poly factored into (t-5)(t-9)(t+12)

So we have the potential

a=5,b=9;

a=5, b= -12;

a=9, b=5;

a=9, b=-12;

a=-12, b=5;

a=-12, b=9;

And for these, I got

52/15, -11/15, 4, 3/5, -3, 11/5 when plugging in to my equation

but it said that I was wrong. I was wondering why. Then i put it into wolfram and it gave 52/15, -11/15, 3/5, -3, 11/5

this was also wrong as I expected, since computer may miss a few pointers.

Can anyone show me where I Was wrong? Thanks in advance!

Best,

Jimmy

MathProblemSolver101 May 29, 2021

#1**0 **

https://web2.0calc.com/questions/some-of-my-questions-got-deleted-question

hope this helped Jimmy neutron

Guest May 29, 2021

#2**+1 **

Setting a, b, and c is really smart.

a = 3x

b = 5y

c = -6z

3x + 5y - 6z = 2

a + b + c = 2

5xy - 10yz - 6xz = -41

ab + bc + ac = -123

xyz = 6

abc = -540

x^3 - 2x^2 - 123x + 540

(x - 5)(x - 9)(x + 12) # I don't know how to factor cubic equations, I just plugged it into a calculator.

x = 5, 9, -12

a = 3x

b = 5y

c = -6z

a = 5, b = 9

5/3 + 9/5 = 52/15

a = 5, b = -12

5/3 - 12/5 = -11/15

a = 9, b = 5

9/3 + 5/5 = 4

a = 9, b = -12

9/3 - 12/5 = 3/5

a = -12, b = 5

-12/3 + 5/5 = -3

a = -12, b = 9

-12/3 + 9/5 = -11/5

Everything looks right to me, I'm not sure why it's wrong. :((

Looking at Asinus's answer from the link guest sent, he had the same aproach too.

=^._.^=

catmg May 29, 2021

#4**+1 **

Thanks for your post and thoughtful time!

And how I factor a cubic equation, is I use the rational root theorem to find possible roots. Then I use synthetic division one by one to rule out the false ones. Then it just makes it into (x-n)(x-m)... where n,m,etc. are my roots

MathProblemSolver101
May 30, 2021